Modelling the implications of regular increases in tobacco taxation in the tobacco endgame. - Cobiac, L; Ikeda, T; Nghiem, N; Blakely, T; Wilson, N (BMJ Publishing Group, 2014)
OBJECTIVE: We examine the potential role for taxation in the tobacco endgame in New Zealand, where the goal is to become 'smokefree' (less than 5% smoking prevalence) by 2025. DESIGN: Modelling study using a dynamic population model. SETTING AND PARTICIPANTS: New Zealand, Māori and non-Māori men and women. INTERVENTIONS: Annual increases in tobacco excise tax of 5%, 10%, 15% and 20% (with 10% reflecting the annual increase recently legislated by the New Zealand Government to 2016). RESULTS: With a continued commitment to annual 10% increases in tobacco excise tax, in addition to on-going Quitline and cessation support, New Zealand's smoking prevalence is projected to fall from 15.1% in 2013 to 8.7% (95% uncertainty interval 8.6% to 8.9%) by 2025. This is compared to 9.9% without any further tax rises. With annual tax increases of 20%, the prevalence is projected to fall to 7.6% (7.5% to 7.7%) by 2025. The potential reductions in smoking prevalence are substantial for both Māori and non-Māori populations, although annual tax increases as high as 20% will still only see Māori smoking prevalence in 2025 approaching the non-Māori smoking levels for 2013. Scenario analyses did not suggest that growth of the illicit tobacco market would substantively undermine the impact of tobacco tax rises. Nevertheless, unknown factors such as the gradual denormalisation of smoking and changes to the 'nicotine market' may influence sensitivity to changes in tobacco prices in the future. CONCLUSIONS: Regular increases in tobacco taxation could play an important role in helping to achieve tobacco endgames. However, this modelling in New Zealand suggests that a wider range of tobacco endgame strategies will be needed to achieve a smoke-free goal of less than 5% prevalence for all social groups-a conclusion that could also apply in other countries.